OPTIMAL SOLUTION FOR GENERATOR MAINTENANCE SCHEDULING PROBLEM - JULIA FITRI (NIM : 10108031); Pembimbing : Novriana Sumarti, Ph.D, HARNI
Currently, generator maintenance schedulling become a problem that important to be resolved because it involves the demand of power by public. Generator is a machine that can not work continuously. Therefore, the generator must undergo regular maintenance in order to work optimally. Maintenance of these generators are not expected to interfere with its function as a producer of electric power required by the community each week. This problem will be solved by simulated annealing and genetic algorithms. Some of the cases discussed are the process of optimization with and without penalty. The existence of the penalty factor allowing bad solutions include but are penalties. Modification of the above issue is the frequency of different generator maintenance schedule, for example once a year and two years, and maintenance schedules that are adaptive to changes in the middle of the running time.